ROLE OF PHYSICAL EDUCATION IN DEVELOPING STUDENTS YASH DEEP SINGH - YASH DEEP SINGH (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The purpose of physical education is basically to make the body healthy, energetic and strong so that the body can become capable of struggle even in worldly adverse situations and can make life meaningful by becoming a means of attaining Purusharth Chatushtya. Students in physical education receive instruction in physical activities that assist keep them in shape. Students who desire to compete in sports receive specific practice sessions and preparation for contests. The capacity and confidence of a pupil to engage in physical activity are developed through physical education. It was incorporated into the academic programme by the Central Board of Secondary Education. The major objective of putting physical education into practice and promoting it is to create physically literate people who have the knowledge and abilities to engage in healthy activities for the rest of their lives. After completing the required training, individuals can continue participating in activities without the assistance of professional trainers. The fundamental goal of physical education is to teach students about how their bodies develop and how to take care of themselves, which includes instruction in everything from basic hygiene to diet management. Knowing exactly what they are doing and why they are doing it requires knowledge. This increases their knowledge in the field of physical education. In this paper we highlight factors that make physical education so crucial and necessary, including how it promotes children's mental health, fosters a spirit of competition, and more. Physical education not only keeps the body in shape, but it also helps children stay healthy physically and mentally